2012
DOI: 10.1055/s-0031-1291487
|View full text |Cite
|
Sign up to set email alerts
|

The role of carbon dioxide insufflation in colonoscopy: a systematic review and meta-analysis

Abstract: Insufflation with CO2 in colonoscopy could decrease abdominal discomfort during and following the procedure, without any additional adverse reactions, warranting routine clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 11 publications
(18 reference statements)
2
74
0
7
Order By: Relevance
“…Many studies evaluated the safety and efficacy of CO2 insufflation for gastrointestinal endoscopy. Two recent systematic reviews and meta-analysis showed that CO2 insufflation is safe in patients without severe pulmonary disease, and is associated with decreased bowel distension and postprocedural pain [53,54] . Furthermore, one of them showed that insufflation with CO2 in colonoscopy could also decrease abdominal pain during colonoscopy [54] .…”
Section: New Endoscopic Technologies For Colon Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies evaluated the safety and efficacy of CO2 insufflation for gastrointestinal endoscopy. Two recent systematic reviews and meta-analysis showed that CO2 insufflation is safe in patients without severe pulmonary disease, and is associated with decreased bowel distension and postprocedural pain [53,54] . Furthermore, one of them showed that insufflation with CO2 in colonoscopy could also decrease abdominal pain during colonoscopy [54] .…”
Section: New Endoscopic Technologies For Colon Examinationmentioning
confidence: 99%
“…Two recent systematic reviews and meta-analysis showed that CO2 insufflation is safe in patients without severe pulmonary disease, and is associated with decreased bowel distension and postprocedural pain [53,54] . Furthermore, one of them showed that insufflation with CO2 in colonoscopy could also decrease abdominal pain during colonoscopy [54] . For these reasons, the use of carbon dioxide insufflation, instead of air, is currently a quality standard to maximize comfort during colonoscopy [55] .…”
Section: New Endoscopic Technologies For Colon Examinationmentioning
confidence: 99%
“…This may be associated with the superior recovery quality of CO 2 insufflation compared with room air insufflation in colonoscopy (36). Therefore, when compared with air insufflation, CO 2 insufflation is expected to reduce the volume of residual gas following ESD, which is a primary cause of patient discomfort associated with this procedure, and consequently prevent the development of abdominal symptoms and problems associated with ESD (5,(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study also reported that CO 2 insufflation was safe and effective during colorectal ESD (15). As CO 2 is absorbed faster than air and is rapidly eliminated through the lungs, CO 2 insufflation is expected to reduce residual gas in both the small and large bowels following ESD, and consequently reduce the abdominal symptoms and complications associated with ESD (15,(22)(23)(24)(25)(26)(27)(28)(29)(30). However, to the best of our knowledge, detailed and quantitative examinations evaluating the effects of CO 2 insufflation on residual gas in the gastrointestinal tract following colorectal ESD have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Хоча деякі пацієнти погоджуються на проведення діагностично-лікуваль-них втручань без медикаментозного забезпечення, використання седативних препаратів пов'язане з вищим рівнем задоволеності пацієнтів [1,2] та якос-ті проведення маніпуляцій [3]. Подолати вищеза-значені ефекти дозволили технологічні досягнення в галузі ендоскопії останніх десятиліть, що поліпшили діагностичні та терапевтичні можливості внаслідок використання більш тонких ендоскопів [11], меншої жорсткості колоноскопів [12], додаткової інсуфля-ції CO 2 [13], методів занурення у воду (під час вико-нання колоноскопії) [14], що дозволило пацієнтам перенести виконання процедур з меншим больовим та психоемоційним навантаженням. Так, протягом останніх 30 років ендоскопічна ретроградна холангі-опанкреатографія (ЕРХПГ) перетворилася у складну процедуру із залученням спеціалізованих операторів, допоміжного обладнання та анестезіологічного пер-соналу.…”
Section: вступunclassified